A rich locality in South Kensington: the fossil hominin collection of the Natural History Museum, London. (16th February 2015) - Buck, Laura T.; Stringer, Christopher B.; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> The primacy of fossils in the Natural History Museum (NHM) goes back to the very origins of the Museum, but the first fossil hominins in the collections were probably the Upper Palaeolithic remains from Bruniquel, which were accessioned in 1864. This founded a collection which has continued to expand into this century. While there have been many compilations and descriptions of the fossil hominin collection at the NHM over its long history, to our knowledge no‐one has prepared a review of the collection itself. The intention of the current paper is to synthesize earlier sources with accounts of new finds, revised chronologies and rediscovered treasures in order to illustrate the breadth and continuing importance of the fossil hominins curated at the NHM. We list and discuss all the hominin material known or thought to pre‐date the Holocene. These form a collection of great importance, both in terms of their research value and history of science. With the application of new investigative techniques such as aDNA and microCT, the material remains central to palaeoanthropological research in the 21st Century. Copyright © 2015 John Wiley & Sons, Ltd.